HUBUNGAN BEBAN KERJA DAN KELELAHAN KERJA DENGAN KINERJA PERAWAT DI RUANG RAWAT INAP DI RSU GMIM BETHESDA TOMOHON - Akay, Tinny Wilhelmina Mesbry; Berhimpong, Vivi Meiti; Tungka, Kartini Estelina (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Background: In the hospital, fatigue, and workload are factors that can affect the performance of nurses so that they can cause mistakes in working for nurses, and can endanger the health and safety of patients and nurses. Research Objectives: To analyze the relationship between workload and work fatigue with the performance of nurses in the inpatient room at RSU GMIM Bethesda Tomohon. Method: This type of research is quantitative with a research design using a cross-sectional approach. The population is 70 respondents with a sample of 65 respondents. The sampling technique uses purposive sampling. The independent variables in this study are workload, work fatigue, and the dependent variable of nurse performance. The research data were analyzed univariately and bivariate using the Spearman rho test. Results: The test results show that the significance value is 0.018 ˂ α = 0.05 and the correlation coefficient is 0.293. This means that there is a relationship between workload and nurse performance with weak relationship strength. The study’s results showed a significant relationship between work fatigue and nurse performance showing a significance value of 0.009 ˂ 0.01 and a correlation coefficient of 0.321 with weak relationship strength. Conclusion: This study concludes that workload and work fatigue are factors related to the performance of nurses at General Hospital GMIM Bethesda Tomohon.